RELIGIOUS MODERATION: AN APPROACH OF RELIGIOUS LIFE IN INDONESIA - Demsy Jura (Jurnal Inovasi Penelitian, 2021)
Religious moderation in Indonesia is one of the choices that can be taken as an effort to reduce religious radicalism which greatly disturbs the stability of the state’s security. The pluralism of Indonesian society demands the right attitude in living a religious life, meaning that every religious follower is required to practice his religious beliefs correctly while respecting the existence of other religious followers. Religious moderation provides new choices and is in the middle axis in living a religious life, namely between religion’s radicalism and religion’s liberalism.